Konsep Brahmān Dalam Muṇḍaka Upaniṣad Dan Relevansinya Terhadap Multikulturalisme Di Indonesia - Puspo Renan Joyo; Siti Murtiningsih; Sindung Tjahyadi (Jurnal Penelitian Agama Hindu, 2022)
This paper examines two issues, which are the concept of Brahmān in the Muṇḍaka Upaniṣad from theological and philosophical studies; and the relevance of the concept of Brahmān and multiculturalism in Indonesia. The first study is a theological study to examine the concept of Brahmān based on beliefs that are supported by the truth of the scriptures, while a philosophical study is to understand the concept of Brahman from the aspect of rationality or reason. The philosophical approach is divided into three arguments, namely; ontological, cosmological, and morality. The second study is to find the relevance of the concept of Brahmān, both from a theological and philosophical perspective towards multiculturalism in Indonesia. The results of the study are to provide insight of the concept of Brahmān as well as its values that are relevant to the discourse on Indonesian multiculturalism and its challenges. This study applied a factual historical research model regarding texts with material objects of the Brahmān concept in the Muṇḍaka Upaniṣad. The main data of this study was the Muṇḍaka Upaniṣad, by Radhakrishan. The data was obtained through library research and then processed using an interactive model through the stages of data condensation, data display, drawing, and verifying conclusions. This study used interpretation and description data analysis. The results of this study indicate that Brahmān is the only reality, the highest, and absolute. There are two aspects of Brahmān, the Nirguṇa (transcendent-impersonal) and Saguṇa (immanent-personal) aspects. The concept of Brahmān in the Muṇḍaka Upaniṣad and multiculturalism has relevance and is in the same spirit.